Sensory processing characteristics and eating behaviors in preschool children -- an occupational therapy perspective - Argenti, Melissa, author; Davies, Patricia, advisor; Gavin, William, committee member; Bellows, Laura, committee member; Johnson, Susan, committee member (Colorado State University. Libraries, 2013)
Childhood obesity is a serious problem in the United States, and early childhood may be a critical time to implement obesity prevention efforts. Understanding a child's eating habits, such as picky-eating and food neophobia, is critical in intervention planning and helping a child develop healthful eating behaviors that lead to nutritionally adequate diets. Yet, to date, there is little research about a child's sensory processing characteristics and how it relates to their eating behaviors. There is currently a research study occurring in Colorado entitled, "A Longitudinal Study to Assess if the Effectiveness of a Preschool Nutrition and Physical Activity Program is sustained in Elementary School" and children's eating behaviors is just one area of data being collected through the means of a Tasting Panel and their parent's report. Through a partnership with this study, the purpose of this research was to understand the relationship on sensory processing characteristics and eating behaviors in preschool children, using caregiver surveys and data from an in-person Tasting Panel completed with preschoolers. This research study also examined the accuracy of a parent's report of their child's behavior in relation to their actual behavior, in addition to examining the reliability in certain sections of the Sensory Profile Caregiver Questionnaire. Finally, this study examined children's oral sensory processing in relationship to other areas of sensory behaviors. Overall, there was a significant relationship between the number of children's food refusals, as measured by the in-person Tasting Panel and two specific sensory processing characteristics ("gags easily" and "craves certain foods"). There was a significant relationship between children's food refusals and their parent's report of food neophobic or picky eating behaviors, demonstrating consistency in parent's report and confirming parental awareness of their child's eating difficulties. Test-retest reliability analyses of the total score for the oral sensory processing questions included in the Sensory Profile Caregiver Questionnaire were not significant, which may have been due to the different contexts that the questions were administered; for time one the questions were included in the Child Feeding Survey and for time two the questions were included in the full Sensory Profile Caregiver Questionnaire. In addition, there was a significant relationship between oral sensory processing and two other domains of sensory processing, the tactile domain and the multisensory domain. This is an important finding for healthcare professionals working with children with oral sensory processing difficulties, as other sensory evaluations may be needed to better treat the child. If parents and healthcare professionals can understand a child's sensory processing behaviors in greater detail, a child may be better served, which ultimately results in life long healthy eating behaviors.
Keywords: childhood obesity; eating behaviors; LEAP; occupational therapy; oral sensory processing; picky eating